Social research & reflexivity content, consequences and context - May, Tim, 1957- (SAGE, 2011)
What are the critical gaps in thinking about reflexivity and social research? How is reflexive practice shaped by the contexts and cultures in which researchers work? How might research practice respond to twin demands of excellence and relevance in the knowledge-based economy?